Gene mapping of a novel glossy mutant in Brassica napus L. based on whole genome resequencing technology - WEN Yancheng; HE Junping; CAI Dongfang; ZHANG Shufen; ZHU Jiacheng; WANG Jianping; CAO Jinhua; ZHAO Lei; WANG Dongguo; LIU Yizi (浙江大学学报. 农业与生命科学版, 2023)
Epicuticular wax in the rape is one of the protective barriers in stress environments. We previously reported one glossy mutant DL22B077-1 in Brassica napus L. controlled by a pair of dominant genes. In order to further understand its genetic mechanism, the glossy genes in the F2 population were mapped by whole genome resequencing technology and bulk segregated analysis (BSA) in this study. A total of 1 0661.75 Mb of clean bases were obtained, with an average Q30 of 92.99%, an average mapping ratio of 97.73%, an average sequencing depth of 24×, and an average coverage ratio of 82.06%, which indicated that the sequencing quality was high. In addition, the correlations between the glossy characters and markers of single nucleotide polymorphism (SNP) and insertion-deletion (In-Del) in genomic domains were analyzed. In the SNP marker, seven associated regions and 1 509 genes on five chromosomes were obtained. In the In-Del marker, 15 associated regions and 2 633 genes on 11 chromosomes were obtained. The final association results were the intersection of two kinds of markers, which was the 1.79 Mb associated region from 8.60 Mb to 10.39 Mb on chromosome C8, and there were a total of 130 candidate genes in this region. A total of 119 genes in the 130 candidate genes were annotated, which participated in the construction of cellular components and were involved in molecular functions and biological processes. In B. napus, DL22B077-1 was the first glossy mutant whose glossy genes were located on chromosome C8, so it was a novel glossy mutant. The above results lay a theoretical foundation for breeding rape varieties with high and stable yields and improving resistance cultivation techniques.